EFFECTS OF MELATONIN ON BLOOD PRESSURE IN THE ELDERLY - F.D. BOBOEV; R.G. SOKHIBOV; SH.F. ODINAEV; A.A. UMAROV; SH.A. SULAYMONOVA (Avicenna Tajik State Medical University, 2024)
The study provides literature data on the impact of melatonin on blood pressure (BP) in elderly individuals with arterial hypertension (AH). AH is a significant risk factor for cardiovascular diseases (CVDs) and is a key focus of medical research. Melatonin, which plays a crucial role in the body's regulatory mechanisms, particularly when its production is disrupted, can significantly influence the development of AH. Melatonin is not a specific treatment for a particular disease but a multifunctional element that helps maintain homeostasis. Combining melatonin with antihypertensive therapy in elderly individuals with AH has been found to lead to more effective treatment outcomes. Exploring the effects of melatonin on BP levels in elderly individuals with AH is of great scientific interest, especially in understanding the relationship between individual melatonin secretion characteristics and predisposition to cardiovascular complications. This topic requires further research for a deeper understanding. Over 400 sources were analyzed on various aspects of the impact of melatonin on BP levels using materials from the PubMed and Google Scholar electronic databases. Out of these, 44 sources were selected and included in the study, considering relevant keywords.